VOCATIONAL TRAINING OF HIGHER EDUCATION TEACHERS IN MAGISTRACY: EXPERIENCE OF THE EUROPEAN COUNTRIES - Protsenko, Olena B. (Educological discourse, 2015)
The article is devoted to the problem of the higher teachers’ training in the Magistracy of European countries. The topicality of this problem is conditioned by the necessity to implement the foreign experience for qualitative higher teachers’ training in Ukraine. The ways of Master’s degree receiving in Europe are examined; the experience of Master’s degree programs’ implementation in the United Kingdom, Austria, France, Greece is presented. It is proved, that the programs have practical directivity and they develop the skills of lifelong learning.